Synthesis and characterization of barium hexaferrites derived from steel waste using salt-melt technique - Che Muda, Nor Nadhirah (2017)
This project focused on the synthesis of barium hexaferrites derived from steel waste (also known as mill scales). The steel flakes were ball milling for several hours to form fine powders. The fine powders are purified using magnetic separation technique (MST) and Curie temperature separation technique (CTST). The purified steel waste powder then oxidized at 500 ºC to form hematite, Fe2O3. Fe2O3 powder was characterized using X-ray Fluorescence (XRF), Fourier Transform Infrared spectroscopy (FTIR), X-ray diffraction (XRD) and energy-dispersive X-ray analysis (EDX). The XRD and XRF results indicate the purified powder obtained are iron oxide Fe2O3 (ICDD 98006-9763) and show that the obtained powders have high content of Fe2O3 for about 99.051%. The Fe2O3 were used to synthesize BaFe12O19 by using salt-melt method. The samples were synthesized using different powder to salt weight ratio of BaCO3 + Fe2O3 and ammonium nitrate salt (NH4NO3). The NH4NO3 was melted at 170 ºC. The mixture of BaCO3 and Fe2O3 were added into the NH4NO3 melt solution and kept stirring for several hours using magnetic stirrer under control temperature of 170 oC. The heating temperature was then increased up to 260 oC for 24 hours to produce ash powders. The XRD show the peak of BaFe12O19 for all the samples and the presence of small amount of impurity Fe2O3 for sample’s ratio 1:5 and 1:6. Based on FTIR spectra, the bands appears at 542.71 cm-1 and 432.48 cm-1 corresponding to metal-oxygen bending and vibration of octahedral sites of BaFe12O19. The FESEM images shows that the grains of the samples appear to stick to each other and agglomerate at different masses throughout the image with the grain size 5.26, 5.88, 6.14, 6.22 and 6.18 μm for ratio 1:3, 1:4, 1:5, 1:6 and 1:7 respectively. From the VSM analysis, the magnetic properties of sample with a ratio 1:3 shows the highest value of coercivity Hc of 1317 Oe, saturation magnetization Ms of 91 emu/g and remnant Mr of 44 emu/g. The dielectric measurement shows that the BaFe12O19 samples have high dielectric loss and low ac conductivity. The complex permeability measured from VNA shows that the real part of permeability in the range of 1.0 to 1.2. The imaginary parts of permeability is in the range of 0 to 0.1. The minimum reflection loss is approximately around -3.9 dB to -4.33 dB for all samples.The first matching frequency in average of 8.8 GHz are due domain wall resonance for all samples while natural resonance appears at second matching frequency in average of 11.0 GHz. This project is significance have potential for used in the low cost, recycle approached permanent magnet fabrication that potentially used in motor, loudspeakers and electromagnetic (EM) absorber applications.